Pengaruh Self-Efficacy, Career Planning, Social Support Terhadap Kesiapan Kerja Mahasiswa Akuntansi Gen Z - Aziz, Alif Thareq; Baihaqi, Baihaqi; Handayani, Fitri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study thoroughly explores the variables that influence the work readiness of accounting students from Generation Z, focusing on self-efficacy, career planning, and social support. The research employed a quantitative approach using multiple linear regression analysis. Data were collected through a Likert scale (1–5) questionnaire from 349 Generation Z accounting students who had completed at least their sixth semester. The data were analyzed using IBM SPSS Statistics version 20, including validity, reliability, and classical assumption tests. The results show that all three variables have a significant and positive effect on work readiness, with regression coefficients of 0.461 for self-efficacy, 0.475 for career planning, and 0.426 for social support. Career planning emerged as the most dominant predictor with the highest standardized beta value (0.443). These findings indicate that enhancing self-efficacy through practical experiences, structured career planning, and strong social support from families, lecturers, and peers plays a crucial role in improving students’ work readiness. This study highlights the importance of a holistic approach that integrates students, educational institutions, and social environments. Future research is recommended to incorporate additional variables such as digital adaptability and emotional intelligence and to apply longitudinal and mixed-method approaches for a more comprehensive understanding.